Preserving local biodiversity through crop diversification. Issue 3 (5th October 2021) - Strobl, Eric
Abstract: Using the case study of birds and food crops, we investigate whether diversifying crop production can enhance preservation of local biodiversity. To this end we combine annual bird survey data, high resolution land use data, and phylogenetic trees to create a landscape level panel data set covering the conterminous United States for over a decade. Our econometric analysis shows that greater local food crop hetereogeneity increases local avian diversity, although this is spatially limited. Supplementary county level data provides evidence that more food crop diversity is unlikely to be at the cost of lower revenues.